Reconstruction of The Concept of Maḥram in Women’s Safar Based on Ibnu Qayyim al-Jauziyyah’s Legal Change Theory - Mughniatul Ilma (Institut Agama Islam Negeri Batusangkar, 2021)
This paper aims to analyze the legal thought about the prohibition of women traveling without maḥram and attempt to reinterpret the Prophet's hadith regarding the prohibition through contextualization and reconstruction. The theory of legal change by Ibn Qayyim al-Jauziyyah was chosen in this paper to explain the characteristics of the Islamic law that can change and accept change. The universal message contained in the hadith cannot be ignored by simply sticking to the text. The hadith regarding the prohibition of traveling for women without a maḥram has a very different context from the present context. This can be proven by the aspects that become factors of legal change according to Ibn Qayyim al-Jauziyyah including time (azminah), place (amkinah), condition (ahwāl), intention/motivation (niyāt), and tradition (‘awāid). Based on these aspects, it can be understood that the urgency of the maḥram in women's journey is intended as a guarantee of security from the dangers that were very likely to be experienced women at that time. In contrast to the present context, which has experienced rapid development in the fields of technology, information, transportation, which provide more access, comfort, and security. Efforts to protect women have been legitimized through existing legal norms.